MENTAL ILLNESS OF THE MAIN CHARACTER IN THE MOVIE DADDY’S PERFECT LITTLE GIRL DIRECTED BY CURTIS CRAWFORD - Restalia Restalia; Sulhizah Wulan Sari; Retno Dwigustini (Jurnal Scientia, 2023)
Mental illness is a mental or psychological disorder or a health condition that affects an individual's thoughts, emotions, and behaviors in their daily life. The purpose of this research is to analyze and understand the mental illnesses experienced by the main character, to identify the types of mental illnesses and factors that contribute to the main character's mental disturbances, and how to treat the people of suffering the mental illness. In this study, the writer utilizes a qualitative descriptive research method, using images and dialogue from the film "Daddy's Perfect Little Girl" to depict the mental illnesses experienced by the main character. The findings of this research reveal that are (1). Trauma disorder, personality borderline disorder, paranoid personality disorder, antisocial personality disorder, and psychotic disorder (2). The factor of mental illness experienced by Ella’s character in the film is because Ella saw violence in the past and lost her mother (3). Her father takes her to a rehabilitation hospital for treatment and provides extra support to facilitate her recovery. This research is essential to be conducted because it can be useful for writer and readers, so they can be aware of the symptoms of mental illness so that treatment can be carried out quickly before trauma occurs.